Multi-Authored Articles and the Real Contribution of the Researcher in the Convergence of Writing with the Three-Dimensional Measurement CAWH: Aerospace Engineering Field - Somayeh Ghavidel; Nosrat Riahinia; Farshid Danesh; Abdolreza Noroozi Chakoli (پژوهشنامه علم سنجی)
Purpose: Today, researchers encounter challenges in scientific collaboration and the alignment of results with their peers. This study aims to evaluate the accuracy of identification and the extent of researchers' genuine participation in the convergence of multi-authored articles written by aerospace researchers, utilizing the three-dimensional Collaborative Author Writing Hierarchy (CAWH). Author associativity is a concept closely linked to scientific collaboration and multi-authored publications. The complexity of knowledge and the increasing demand for specialization and interdisciplinary skills have shaped scientific participation. Aerospace researchers and specialists are pivotal in conducting scientific and industrial research within the aerospace sector, focusing on technology development and providing support and guidance to fellow researchers. The aerospace industry is multi-faceted, strategic, and dynamic, possessing significant potential for wealth generation, economic development, enhancing national competitiveness on the global stage, job creation, and export opportunities. In various fields of study, numerous indicators have been established for observing, monitoring, and quantitatively and qualitatively evaluating researchers' publications, leading to the introduction of diverse metrics accordingly.Methodology: The research is applied in nature and employs an analytical approach. To assess the improvement in accurately identifying the author's true contributions in published articles, a composite measure that examines multiple dimensions has been utilized. The research outputs of aerospace researchers were analyzed, drawing on data categorized under "Engineering, Aerospace" in the Web of Science Core Collection (WOSCC). English-language articles published from 1945 to 2021 were extracted for this study. Data extraction was conducted on February 4, 2022, a Friday. The current research community encompasses all aerospace researchers from 1945 to 2021, comprising 153,994 records indexed in the Web of Science Core Collection (WOSCC). The total number of authors is 161,156, of whom 154,450 researchers with identifiable names (without sampling) were examined. The total number of citations is 2,617,712. Data extracted from the scientific website during the research period were analyzed. In this research, two tools, namely the "MiMFa Scraper, were employed to gather detailed information about each author. Additionally, another tool was utilized to match the gauge information with PHP (Hypertext Preprocessor). This tool is considered part of the DataLab software suite. Ravar PreMap software was also used to standardize the data. To normalize the data, the codes developed in the DataLab software were implemented. Excel 2016 was also utilized to extract data from various websites using PHP. The CAWH measure is defined as the average number of weighted citations based on co-author credit for a researcher.Findings: The results of the H-weighted co-authorship index indicate "Florian Menter" (from ANSYS Germany GmbH), "Chae M. Rhie" (from Raytheon Technologies USA), "Philippe R. Spalart" (from Boeing), "Edward F. Crawley" (from Massachusetts (from the Institute of Technology (MIT)), "Irving Reed" (from university (from Southern California) are in rank fifth ranks of among based on the CAWH index. This measure was used to calculate the utilizing assessment of each author in writing a multi-author article.Conclusion: The emphasis on recognizing researchers' contributions in article writing will be beneficial and effective for both researchers and the scientific community. Acknowledging researchers' involvement in writing allows them to showcase their contributions and achievements fairly and transparently. This approach enables researchers to properly receive their scientific credit and build their reputation, thereby gaining a competitive advantage within scientific communities. Within research teams, the implementation of this measure will enhance collaboration, facilitate the division of labor, and more equitably determine the rights and benefits of each team member. This approach fosters active collaboration and enhances the productivity of research teams. It enables research organizations and universities to conduct more accurate scientific evaluations of individuals and allocate resources based on equitable distribution and participation. Additionally, this method can improve transparency and build trust within research organizations. Consequently, it can help cultivate a culture of participation and cooperation within scientific communities. This approach can foster healthy, justice-oriented competition in science and enhance the quality of research. The evaluation offers readers and the scientific community detailed information about the authors and their collaborators involved in the research. This transparency enables readers to better assess the contributions and expertise of the article’s authors, thereby increasing their trust in the results and citations presented. Overall, acknowledging the participation of researchers in writing articles supports the scientific process and advances the field of science. This approach offers guidance for justice, transparency, cooperation, and the enhancement of research quality within scientific communities. It fosters an environment conducive to scientific development and progress, which can be assessed and refined using the index introduced in this study.